Crisis Leadership In The Incident Command System - Fitriani Fitriani (Musamus Journal of Public Administration, 2021)
The purpose of this research is to describe the activities of crisis managers or also known as ICS (Incident Command System). At the regional level this management is given to the BPBD in which a pragmatic crisis leader is needed; react quickly to change (responsive); firm in implementing compliance, including the schedule through the performance management scheme (rewards and consequences); and have good articulation in conveying communication so as to increase the trust of stakeholders, both internal and external. This type of research is qualitative using the method used is literature study. The results of this study are basically the Incident Commander can come from any circle as long as he is professional and is able to make decisions quickly and accurately with all the consequences which are the characteristics of Crisis Leadership